Economic areas under financial stability - Ramlall, Indranarain (Emerald Publishing Limited, 2018)
The world is presently buffeted by many challenges, some of which manifest in new forms, such as Fintech and cryptocurrencies, while some challenges prevail out of the legacy trailed behind by the 2007 global financial crisis. Financial stability represents a highly complex and multi-dimensional concept. This being so, a sound and holistic financial stability assessment requires a focus not only on the distinct sectors which make up an economy but also on certain key economic areas. 'Economic Areas Under Financial Stability' examines several core areas which interact directly with financial stability. A comprehensive consideration is given to local and international developments, the payment and settlements system, reserves, derivatives,and exchange rates. The book examines critical developments on both the local and international fronts, the systematic risks which characterise the payment and settlements system, different instruments of derivatives, and the significance of fiscal and monetary policy in relation to exchange rates. This book will prove valuable to central bankers, economists, and policy-makers who are involved in the field of financial stability, as well as researchers studying the field.
Keywords: Economic stabilization.; Business & Economics -- Finance -- General.; Finance.; elektronické knihy; electronic books